Milner, Beit and Smuts - Murray, Bruce (My University, 1976)
The movement to establish a university on the Witwatersrand was initiated immediately after the Anglo-Boer War of 1899-1902. It was a movement inspired by the new British regime. Both Lord Milner, the Governor of the Transvaal and Orange River Colony and High Commissioner for Southern Africa, and Joseph Chamberlain, the British Colonial Secretary, looked towards the establishment of a teaching university on the Rand. As Joseph Chamberlain put it in his celebrated speech at the Wanderers Club on 17 January 1903s: “If I were to point at this time to what, in my opinion, is the most urgent need of this community, I should say it was the immediate provision of a High School, efficient in every respect; and of a Scientific University specialised according to the needs of the great industries of the community. I can hardly doubt that an appeal to local patriotism to those who have made their fortune here will not be without its effect, and that before long Johannesburg will possess a University; which in its own lines will be superior to anything that now exists in the world”. British imperialist strategy, mining capital and the requirements of the gold mining industry of the Witwatersrand, a determination to open up the professions to locally trained persons, the assertiveness of the English-language groups in the Afrikaner North, and Johannesburg civic pride, provided the main thrusts behind the movement for the foundation of a university in Johannesburg. The counterthrusts, which served to delay the arrival of a full-fledged university on the Rand, stemmed from the vested interests of Cape Town, the rivalry of Pretoria, Afrikaner resistance to British cultural hegemony in South Africa, an immense amount of prejudice to the notion of ‘sinful’, ‘speculative’ and ‘turbulent’ Johannesburg as providing the seat for a university, and the machinations of Jan Christiaan Smuts. Strictly speaking, the story of Wits as a single institution, although with bewildering changes in name and status during its first two decades of formative struggle and development, dates from the Transvaal Technical Institute, founded in 1903. Its antecedents were nonetheless to be found in the Cape, and in the establishment at Kimberley of a school of mines.
African Studies Seminar series. Paper presented October 1976
Keywords: Education, Higher. South Africa